(Re)Connecting Analytic Philosophy and Empirical Research: The Example of Ritual Speech Acts and Religious Collectivities - Rota, Andrea (Sophia, 2022)
In this paper, I demonstrate how philosophical insights and empirical research on the use of religious language can be fruitfully combined to tackle issues regarding the ontology of religious collectivities and the agency of group actors. To do so, I introduce a philosophical framework that draws on speech act theory and recent advances in the fields of collective intentionality and social ontology, with particular attention paid to the work of Raimo Tuomela. Against this backdrop, I discuss a brief case study based on my fieldwork among Jehovah’s Witnesses in Switzerland and Germany. In particular, I call attention to the structure of the Witnesses’ ritual interactions and to the types of speech acts that are performed in their congregational settings. I argue that the communicative framework provided by these rituals is particularly suited to the creation of genuine group intentions that cannot be reduced to the private intentions of the individual group members. In conclusion, I argue that most of the language used in religious contexts does not deviate much from everyday language; however, particular ritual settings can elicit performative effects and constitute new social realities that can have a concrete impact on both individuals and religious groups.